Genome-Wide Association Study of Genetic Control of Seed Fatty Acid Biosynthesis in Brassica napus - Gacek, Katarzyna; Bayer, Philipp E.; Bartkowiak-Broda, Iwona; Szala, Laurencja; Bocianowski, Jan; Edwards, David; Batley, Jacqueline (Frontiers in Plant Science, 2017)
Fatty acids and their composition in seeds determine oil value for nutritional or industrial purposes and also affect seed germination as well as seedling establishment. To better understand the genetic basis of seed fatty acid biosynthesis in oilseed rape (Brassica napus L.) we applied a genome-wide association study, using 91,205 single nucleotide polymorphisms (SNPs) characterised across a mapping population with high-resolution skim genotyping by sequencing (SkimGBS). We identified a cluster of loci on chromosome A05 associated with oleic and linoleic seed fatty acids. The delineated genomic region contained orthologs of the Arabidopsis thaliana genes known to play a role in regulation of seed fatty acid biosynthesis such as Fatty acyl-ACP thioesterase B (FATB) and Fatty Acid Desaturase (FAD5). This approach allowed us to identify potential functional genes regulating fatty acid composition in this important oil producing crop and demonstrates that this approach can be used as a powerful tool for dissecting complex traits for B. napus improvement programs.